Dukungan Sosial Pada Caregiver Pasangan PenderitaDiabetes Mellitus Tipe 2 - Sujatmiko, Eka Pangestika, Dr. Eny Purwandari, M.Si (2016)
The purposes of this research is to understand, explores, and discribes about social support on caregiver spouse of patiens with type 2 diabetes mellitus. Researcher uses qualitative method with research informants consisting of 3 key informants and 7 supporting informants. Key informant is caregiver, meanwhile supporting informant is person close to caregiver and know about caregiver's activity in caring patiens of DM. In this research, researcher uses interview method and obsevations (self behavioral checklist and naturalistics) as data collection instrument. the result of the research indicated that the caregiver are subjected to stress pertaining to emotion and give the impact physically, emotion, cognitive and behavior. The Caregiver solve the problems came up with do coping at emotional focused coping and support social received from the people around. Caregiver have the whole social a form of support for tending, however support the most widely accepted by caregiver is support emotional and support instrumental. Then, there are pattern intermediate improve the welfare of psychological when the pattern is interwoven two directions, where caregiver and the patients of DM understand each other the condition of one with another. Social support which is received by caregiver influenced by education background, gender, old caring, age and job.